Lesbian, Gay and Bisexual teachers' negotiations of civil partnership and schools: ambivalent attachments to religion and secularism. Issue 3 (4th May 2018) - Neary, Aoife; Gray, Breda; O'Sullivan, Mary
ABSTRACT: As legal structures for same-sex relationships are introduced in many contexts, the politics of sexuality are negotiated along religious/secular lines. Religious and Lesbian, Gay, Bisexual, Transgender, Queer (LGBT-Q) rights are pitted against one another such that LGBT-Q lives often assumed to be secular. Schools are crucibles of intermingling religious, secular and equality discourses and this complexity is carefully negotiated by LGBT-Q teachers in their everyday lives. Drawing on a study with LGB teachers as they entered into a Civil Partnership in Ireland (a legal structure in place for five years prior to enactment of Marriage Equality in 2015), this paper captures a 'structure of feeling' – new cultural work done as sexuality norms were in a state of flux. The teachers' accounts unravel the religious/secular binary and provide insight of universal interest into the ambivalent, messy ways in which the politics of sexuality are (re)negotiated across the overlapping social fields of religion and education.